KOMPETENSI PROFESIONAL GURU PENDIDIKAN AGAMA ISLAM SDIT IQRO GEDONG TATAAN DESA SUKARAJA KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN - Sofiya Rosyada (UNISAN JURNAL, 2022)
The learning process organized by some Islamic Religious Education (PAI) teachers is less attractive so that it has an impact on student learning motivation where students look bored and bored even though overall the learning held by Islamic Religious Education (PAI) teachers is good and interesting where the average is the average teacher uses technology in all learning activities so that learning is not fixed in one direction, namely to the teacher, although there are still teachers who use the lecture method in learning activities, this causes student learning outcomes to tend to fluctuate and even experience a decline because activities with the lecture method are less attractive to students. students, students look enthusiastic when in learning activities the teacher uses learning media where learning activities run more varied so that students’ learning motivation also increases. Based on the background of the problem and the identification of the problem above, the formulation of the problem in this study is how the professional competence of Islamic Religious Education teachers in the learning process at SDIT IQRO Gedong Tataan, Sukaraja Village, Gedong Tataan District, Pesawaran Regency? This research is included in the type of field research that is qualitative in nature. Data collection techniques in this study used several methods, namely: (1) observation method, (2) interview method and (3) documentation method. The results of the study indicate that professional competence has been able to be carried out optimally although there is still a need for improvement in all indicators, of the five indicators of professional competence, competence that has been carried out properly and maximally is the use of learning media/technology. The results of the study show that Islamic Religious Education teachers ( PAI) at SDIT IQRO Gedong Tataan, Sukaraja Village, Gedong Tataan District, Pesawaran Regency, has been very good at using learning media/technology ranging from slides, books, record-types, cassettes, laptops, films and LCD projectors, all used properly and systematically in accordance with material to be delivered Keywords: Teacher Professional Competence, Islamic Religious Education